Peran keluarga dan pendidikan kewirausahaan terhadap minat berwirausaha - Grisella Novianti; Maya Malinda (Jurnal Manajemen Maranatha, 2025)
The rapid economic growth has triggered the development of various types of businesses, ranging from micro, small, and medium enterprises (MSMEs) to cafes, which are now becoming increasingly diverse and growing exponentially every day. This phenomenon is also supported by efforts from various universities that include entrepreneurship courses in their curricula across different majors, particularly in management programs. This study has the following objectives, to identify and analyze the role of family and entrepreneurship education on entrepreneurial interest among management students at Maranatha Christian University. This study uses quantitative methods with the use of questionnaires distributed to students from various generations totaling 75 respondents based on the criteria set. The results of this study show that family support does not have a significant impact; this is supported by the fact that many parents are increasingly giving their children the freedom to choose the career they will pursue. Additionally, entrepreneurship education certainly plays an important role, especially in providing the knowledge and skills needed to start and develop a business. This is supported by the organization of Maranatha Entrepreneurship Day (MED), which is one of the efforts of Maranatha Christian University to strengthen the entrepreneurial ecosystem among students, thus producing an innovative and risk-taking entrepreneurial generation. These findings also affirm that although family support does not have a significant effect, the role of the family remains important in supporting students. Additionally, it is crucial for entrepreneurship education to help foster generations of young people with an entrepreneurial spirit, especially among students in management programs. This study will hopefully provide insights into entrepreneurship education and encourage family involvement in supporting the entrepreneurial aspirations of the younger generations.